Trans Subjectifications: Drawing an (Im)personal Politics of Gender, Fashion, and Style. Issue 1 (1st June 2021) - Brice, Sage
Abstract : The lived experiences of gender transition highlight tensions between new and traditional western conceptions of gender and identity, and afford an intimate and unusually broad insight into the mechanisms through which subjectification is gendered and gender subjectivised through daily practices of fashion and style. This experimental, practice-based contribution makes playful and subversive use of a fashion activity book intended for young women and girls to document the author's experiences of gender transition, taking as its cue the notion that the challenges and joys of transition in many ways resemble a form of second adolescence. It draws on an extended ethnographic engagement with gendered social space to explore how we might rethink the question of subjectification in fashion and style as a fundamentally distributed and yet intensely personal social process. The accompanying text maps out some of the project's theoretical impetuses, methodological affordances, and onto-political implications.